2018
DOI: 10.4025/actascianimsci.v40i1.42500
|View full text |Cite
|
Sign up to set email alerts
|

<b>Nutritional composition of pre-dried silage of different winter cereals

Abstract: This study aimed to assess the chemical composition of the forage and pre-dried silage from twelve winter cereals harvested at pre-flowering. We used black oat (Avena strigosa) cv. EMB 139 and cv. IAPAR 61; white oat (Avena sativa) cv. IPR and 126 hp. URS Taura; barley (Hordeum vulgare) cv. BRS Brau and cv. BRS Cauê; wheat (Triticum aestivum) cv. BRS Umbu and cv. BRS Tarumã; rye (Secale cereale) cv. Temprano and cv. BRS Serrano; and triticale (X. Triticosecale) cv. IPR and 111 hp. BRS Saturno. Plants were harv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 24 publications
0
8
0
4
Order By: Relevance
“…According to Heker et al (2020a) and Meinerz et al (2011), more than two harvests seem not to be indicated for rye, because its rapid stem elongation and reduction in the proportion of leaves turn its photosynthetic rate less effective (Horst et al, 2018). On the other hand, this pronounced stem height is a major responsible for the biomass yield (Horst et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…According to Heker et al (2020a) and Meinerz et al (2011), more than two harvests seem not to be indicated for rye, because its rapid stem elongation and reduction in the proportion of leaves turn its photosynthetic rate less effective (Horst et al, 2018). On the other hand, this pronounced stem height is a major responsible for the biomass yield (Horst et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Materials and methods. Different levels of forage peanut (0,20,40, 60, and 80% on FM basis) were added to elephant grass silages. A completely randomized design was adopted, with 5 treatments and 3 repetitions, totaling 15 experimental silos that were opened after 30 days of sealing.…”
mentioning
confidence: 99%
“…In the case of CP, Rotz and Muck (1994) observed similar values when silages were made at the same phenological stage, 7.20%. Horst et al (2018) examined silages of different winter cereals at the pre-flowering stage, comparing the rye cv. Temprano and cv.…”
Section: Resultsmentioning
confidence: 99%